2007
DOI: 10.1007/s00109-007-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COX-2 selective and non-selective NSAIDs on the initiation and progression of atherosclerosis in ApoE−/− mice

Abstract: In this study, we investigated the effects of prolonged administration of the selective COX-2 inhibitors celecoxib and rofecoxib and the non-selective NSAID naproxen on the initiation and progression of atherosclerosis. ApoE(-/-) mice, as well as corresponding wild-type mice, were fed either a normal chow or a high fat Western diet with or without addition of the respective drugs over a period of 16 weeks. Thereafter, aortic lesion size, plasma lipid levels, and COX-2 expression in the plaques were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
4
17
0
1
Order By: Relevance
“…However, the non-selective COX inhibitor naproxen (10 mg/kg, twice a day) did not affect the atherosclerotic lesions in apoE-deficient mice fed a high-cholesterol diet. The same finding using the same dose of naproxen has been reported in apoE-deficient mice fed a high-cholesterol diet in a previous paper 34) ; however, naproxen negated the decreases of all mRNA levels of p22 phox , gp91 phox , ICAM-1, and VCAM-1 by DGLA treatment. The anti-atherosclerotic effect of HC-DGLA was inhibited by naproxen in the HC-DGLA naproxen group; however, there was no significant difference between the HC-vehicle group and HC-DGLA naproxen group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the non-selective COX inhibitor naproxen (10 mg/kg, twice a day) did not affect the atherosclerotic lesions in apoE-deficient mice fed a high-cholesterol diet. The same finding using the same dose of naproxen has been reported in apoE-deficient mice fed a high-cholesterol diet in a previous paper 34) ; however, naproxen negated the decreases of all mRNA levels of p22 phox , gp91 phox , ICAM-1, and VCAM-1 by DGLA treatment. The anti-atherosclerotic effect of HC-DGLA was inhibited by naproxen in the HC-DGLA naproxen group; however, there was no significant difference between the HC-vehicle group and HC-DGLA naproxen group.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, COX-2 selective inhibitors reduce atherosclerotic lesions in apoE-deficient mice fed a high-cholesterol diet 34) . In the present study, to confirm the contribution of COX metabolites of DGLA to the anti-atherosclerotic effect, the effect of a COX inhibitor, naproxen, was examined in DGLA-treated apoE-deficient mice on a high-cholesterol diet.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate the important role of COX-2 in the early development of atherosclerosis and are consistent with our observations that COX-2 inhibition does not alter advanced atherosclerotic lesions. Other studies have also demonstrated that the COX-2 inhibitors celecoxib and rofecoxib did not alter plaque size and COX-2 protein expression in plaque of apo E-/-mice [10,42]. There are conflicting data on the effect of statins on COX-2 expression.…”
Section: Discussionmentioning
confidence: 88%
“…Two other reports showed that selective blockade of COX-2 activity does not have an impact on advanced atherosclerotic lesions [59,60]. Finally, Metzer et al reported that both celecoxib and rofecoxib had no significant impact on the initiation and progression of atherosclerosis in female apoE-knockout mice [61]. These variable results may be attributable to differences in the experimental models and/or protocols used by various investigators.…”
Section: Cyclooxygenase Inhibitors Thromboxane Modulators and Atheroscmentioning
confidence: 95%